Outcomes Following ATG Therapy for Chronic Lung Allograft Dysfunction. Issue 4 (April 2021) - Kotecha, Sakhee; Paul, Eldho; Ivulich, Steve; Fuller, Jeremy; Paraskeva, Miranda; Levvey, Bronwyn; Snell, Gregory; Westall, Glen
Abstract : Background: Chronic lung allograft dysfunction (CLAD) is the major factor limiting survival post lung transplantation (LTx) with limited effective therapeutic options. We report our 12-y experience of antithymocyte globulin (ATG) as second-line CLAD therapy. Methods: Clinical and lung function data were collected on LTx patients receiving ATG. Rate of FEV1 decline (mL/d) was calculated before and after ATG. Partial response to ATG was defined by rate of FEV1 decline improving 20%. Complete response was defined by an absolute improvement or stability in baseline FEV1. Results: Seventy-six patients received ATG for CLAD. Of these, 5 patients who had a clinical diagnosis of antibody-mediated rejection and were treated with plasmapheresis before or after ATG were excluded from analysis. Sixteen (23%) were complete responders, 29 (40%) were partial responders, and 26 (37%) did not respond. Those with CLAD stage 2 or 3 and younger age were more likely to respond. Partial responders had a 65% lower risk of death or retransplant (HR, 0.35; P  = 0.003), whereas complete responders reduced their risk by 70% (HR, 0.30; P  = 0.006). Conclusions: ATG appears to stabilize or attenuate lung function decline in CLAD, which may lead to improved retransplant-free survival. Although certain predictors of response have been identified in this large single-center review, these findings need to be confirmed by a multicenter randomized-controlled trial to determine predictors of response to ATG for CLAD.